A PRELIMINARY STUDY ON THE RESTORATION PROJECT OF ST. VINCENT DE FERRER CHURCH OF DUPAX DEL SUR: PROJECT IMPLICATION - Bobby Argote (SAMPURASUN, 2017)
This research aims to undergo preliminary study on the current condition of Saint Vincent de Ferrer Church of Dupax del Sur, Nueva Vizcaya. It exposes its present status in terms of architectural and structural elements carried out through qualitative and case analysis methods. It also aims to provide awareness regarding its cultural significance to the surrounding community particularly the Isinay minority group and the locals of Nueva Vizcaya. It is also in this research that the researchers highlighted the deteriorating structural and architectural conditions of the church as well as the negative and irreversible impact of uncontrolled and improper restoration works to a cultural treasure such as the church - most of them undertaken by persons that do not possess any qualification or knowledge on restoration and conservation. It also provides an inventory of potential hazards to the people particularly to the congregation when the Church’s deteriorating structural and architectural components are not properly repaired and restored. With this, the researchers highly recommended conservation and restoration of the church and its support structures before elements of nature and man can wipe them out of sight.